AWS Lambda - Chapin, John; Roberts, Mike; Safari eBooks ([Place of publication not identified] : Pearson, 2018)
"More than 3.5 hours of practical video instruction on AWS Lambda--Amazon's Functions-as-a-Service technology--and how to build Serverless applications. The aim throughout this course is not to give you just cookie cutter examples but instead to give you a thorough understanding of the Lambda platform and programming model, so you'll have confidence building your own Serverless applications."--Resource description page.
Presenters, John Chapin and Mike Roberts.
Title from title screen (viewed August 21, 2017).
Keywords: Amazon Web Services (Firm); Web applications -- Development; Application software -- Development; Cloud computing; Electronic books